The Impact of Passive Smoking on Salivary Glutathione Peroxidase and Selenium in Relation to Dental Caries Severity among Five Years Old Children - Shahba’a Munther; Baydaa Hussain Awn; Hiba N. Yassin (Indian Journal of Dental Research, 2023)
Background: It had been found that passive smoking may have the same harmful effect as tobacco cigarettes smoking. Aims: This study was conducted to determine the effect of passive smoking on salivary glutathione peroxidase and selenium in relation to dental caries severity. Settings and Design: The sample consisted of 120 children aged 5 years old, classified into four groups according to the number of cigarettes smoked by their fathers daily: Passive smoking children of 5-10 cigarettes, those of 10–15 cigarettes daily, those of 15–20 cigarettes daily and non-passive smoking children of no smokers indoor (the control group). The sample was further classified according to dental caries severity into three groups: mild (DMFS values <4), moderate (DMFS values from 4 to 8) and severe (DMFS values >8). Methods and Material: Stimulated saliva was collected, and salivary glutathione peroxidase and selenium were chemically analysed. Results and Conclusions: Glutathione peroxidase and selenium were higher among non-passive smoking children than passive smoking children and they were higher among children with mild caries severity than in children with moderate or severe caries severity (p < 0.01). Passive smoking had significant effect in both salivary glutathione peroxidase and selenium (p < 0.01), while dental caries had non-significant effect on them (p > 0.05). In conclusion, passive smoking had deleterious effect in salivary glutathione peroxidase and selenium, while dental caries did not have effect on these two variables. There is no interaction between both passive smoking and dental caries in neither glutathione peroxidase nor selenium, so the effect of passive smoking on these two variables can exceed the effect of dental caries on them.